Pharmacological evaluation of the effects of enzymatically liberated fish oil on eosinophilic inflammation in animal models. (18th April 2022) - Currie, Crawford; Framroze, Bomi; Singh, Dave; Sharma, Deepali; Bjerknes, Christian; Hermansen, Erland
Abstract: The inappropriate activation of eosinophils is a well‐recognized driver of various human inflammatory diseases including asthma, chronic rhinitis, and various gastrointestinal diseases, including eosinophilic esophagitis. Steroids, both topical and systemic, remain a cornerstone of treatment and can be highly effective. However, some individuals suffer side effects, unresolved symptoms, or both. OmeGo, an enzymatically liberated fish oil, has demonstrated anti‐inflammatory and antioxidant properties as well the reduction of the activation, migration, and survival of eosinophils. Two animal models of eosinophilic inflammation were used to further assess OmeGo's profile. A house dust mite model of induced asthma showed a significant reduction in eosinophilic lung inflammation compared to the negative control, linoleic acid. The CRTH2 antagonist fevipiprant showed a similar eosinophilic inhibitory profile to OmeGo. In contrast, cod liver oil had no impact on any measure of inflammation. A guinea pig model of mild intraperitoneal eosinophilia showed a significant reduction in eosinophil activity by OmeGo, assessed by chemotaxis and chemokinesis. Apolipoprotein A‐IV, an endogenous human protein with anti‐inflammatory actions, showed a similar but numerically lower effect. OmeGo therefore combines a consistent antieosinophilic action with the known anti‐inflammatory effects of polyunsaturated fatty acids. Proof‐of‐concept studies in asthma are warranted. Abstract : Modulation of house dust mite and induced eosinophilia models of inflammation.